EVALUATION INFORMATION TECHNOLOGY UTILIZATION OF SCHOOL SUBJECT SCHEDULING USING PIECES FRAMEWORK - Thenata, Angelina Pramana; Prabawati, Andhika Galuh (JUTEI (Jurnal Terapan Teknologi Informasi) (Online), 2018)
Abstract— Information technology has been widely used by several aspects, such as in the scope of business, industry, government, education, and service. The use of information technology in various aspects of spatial planning can help in its business process. One of the use of information technology in the field of education is e-learning, scheduling, financial information systems, and others. SMK N 1 Kaliwungu is one of the schools that already utilize information technology, such as Program Scheduling Subject Schedule. The program helps scheduling in its implementation need to be evaluated to improve more accurate objectives. In this study, will be discussed about system scheduling program Lesson using PIECES Framework. The Framework section is one way of ordering systems or applications related to Performance, Information, Economics, Control, Efficiency, Application Services. Theuse of this framework aims to determine theimplementation of scheduling aids program at SMKN1 Kaliwungu works as a support, enabler, ordriver in the utilization of Information Technology. This research using data from interviews,observations on the curriculum and provision ofquestionnaires to 30 teachers SMKN 1 Kaliwungu. The result of the evaluation obtained from this research is the utilization of scheduling aidsprogram can improve the curriculum performance program can improve the curriculum performance and teaching process to be smoothly without anycollision schedule. The results of evaluation in this research can be said that the utilization of auxiliary programscheduling at SMKN 1 Kaliwungu role as an enabler. Keyword --- Evaluation, Technology Information, PIECESFramework, Schedulling